2017
DOI: 10.1371/journal.pone.0168388
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Nurses’, Preschool Teachers’ and Parents’ Perspectives on Information Sharing Using SDQ in a Swedish Setting – A Qualitative Study Using Grounded Theory

Abstract: Evidence-based methods to identify behavioural problems among children are not regularly used within the Swedish Child healthcare. A new procedure was therefore introduced to assess children through parent- and preschool teacher reports using the Strengths and Difficulties Questionnaire (SDQ). This study aims to explore nurses’, preschool teachers’ and parents’ perspectives of this new information sharing model. Using the grounded theory methodology, semi-structured interviews with nurses (n = 10) at child hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 20 publications
2
28
0
Order By: Relevance
“…Thus, children might either display less emotional and behavioral problems in the preschool setting, or preschool teachers might perceive any such problems as signifying a problem not within the child, but within the preschool environment, thus lowering the proportion of behaviors reported as problematic. In addition, results in a previous study on preschool teachers’ experiences of using the SDQ in the Swedish preschool setting (Fält, Sarkadi & Fabian, ) show that the use of structured assessment forms is considered to be contradictory to the preschool philosophy. Findings from the same study also indicate that teachers are worried about parents’ reactions and fear both making incorrect assessments and labelling children.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, children might either display less emotional and behavioral problems in the preschool setting, or preschool teachers might perceive any such problems as signifying a problem not within the child, but within the preschool environment, thus lowering the proportion of behaviors reported as problematic. In addition, results in a previous study on preschool teachers’ experiences of using the SDQ in the Swedish preschool setting (Fält, Sarkadi & Fabian, ) show that the use of structured assessment forms is considered to be contradictory to the preschool philosophy. Findings from the same study also indicate that teachers are worried about parents’ reactions and fear both making incorrect assessments and labelling children.…”
Section: Discussionmentioning
confidence: 99%
“…Collaboration for early detection and intervention Fält, Sarkadi, and Fabian (2017) included preschool and CHN in their study, and reported that the quality of CHC health check-ups for 3-5year-olds improved when they received SDQ ratings from the preschool teacher as well as from the parents. However, successful implementations of this kind require considerable work at several levels; for example, information sharing, privacy issues, the participation of all parents and normative thinking.…”
Section: Early Interventions In Healthcarementioning
confidence: 99%
“…It would probably be better to engage the parents before the child is formally identified and allowed to receive special support. A Swedish study by Fält et al (2017) found that preschool teachers wished to identify children with difficulties, and at the same time parents viewed preschool teachers as being competent in their ability to estimate this type of behaviour in children. However, both preschool teachers and parents wished that there was a more reliable way to assess children's behaviour.…”
Section: Detection Identification and Intervention In Preschoolmentioning
confidence: 99%
See 1 more Smart Citation
“…In Fält et al. , nurses believed that the CHS does not reach the parents in greatest need when self‐report documents place high demands on parents. Health outcomes in young children are also related to parental literacy .…”
Section: Discussionmentioning
confidence: 99%